Dampak Konsumsi Makanan Tinggi Gula Terhadap Perubahan Mood Pada Gen Z - Isnandhani Rasyid Karimanudin; Ramadhanisa Ihsanty Nursetyanti; Nikmah Aulia Zahrotunnisa; Faridhatun Nikmah; Dikdik Sofyan Safari (Jurnal Ilmu Psikologi dan Kesehatan | E-ISSN : 3063-1467, 2025)
Generation Z, often used as a quick coping strategy to relieve stress and enhance momentary comfort. This literature review aims to examine the relationship between excessive sugar intake and mood changes in Gen Z by synthesizing findings from previous studies. The results indicate that sugar consumption influences stress responses by reducing the activity of the Hypothalamic Pituitary Adrenal (HPA) axis and stimulating the brain’s reward pathways, including the release of dopamine and opioid neurotransmitters that create temporary feelings of pleasure. However, these effects are short-lived and do not contribute to long-term mood stabilization. Excessive sugar intake is also associated with emotional instability, depressive symptoms, emotional eating behavior, and long-term health risks such as obesity. Gen Z tends to consume sweet foods due to academic pressure, social influences, modern lifestyle patterns, and easy access to high-sugar products. Overall, sugar functions more as a temporary reward than a sustainable mood enhancer, highlighting the need for increased awareness and better regulation of sugar consumption among adolescents and young adults.